Restauração de dentes tratados endodonticamente com retentores intrarradiculares: avaliação clínica retrospectiva e revisão sistemática - Garcia, Paula Pontes (2018)
The objectives of this thesis were: 1. to perform a clinical and radiographic analysis of endodontically treated teeth restored with cast metal posts (CMP) or glass fiber posts (GFP) and crowns; and 2. to evaluate the failure rates of anterior and posterior teeth treated with post-and-core restorations by means of systematic review and meta-analysis. In the first manuscript, fifty endodontically treated posterior teeth were restored with 25 CMPs and 25 GFPs at a private dental clinic between 2001 and 2016. Restorations consisted of 12 allceramic crowns, 31 metal-ceramic crowns, and seven composite resin crowns. The radiographic assessment of post-and-core restorations was made in two stages (at baseline and at follow-up). The criteria assessed were: periapical lesion, thickening of the lamina dura, periapical sealing, root attachment to the bone, post-and-core centering, post-and-core length, post-and-core width, post-and-core fracture, root fracture and trepanning. The clinical evaluation was performed by a single calibrated and non-blind examiner. The criteria assessed were: caries, marginal discoloration, marginal integrity, anatomical form, color, occlusion and surrounding tissues Data were analyzed by McNemar’s test, Pearson’s chi-square test, and Kaplan-Meier survival test (α=0.05). The mean follow-up was 67.6 months. For the radiographic evaluation, no statistically significant difference was observed for any of the parameters, comparing initial and final radiography. In the clinical evaluation, anatomical form (p=0.009) and occlusion (p=0.001) showed significant differences when crown restorations were compared (composite resin crowns were outperformed by metal-ceramic and all-ceramic crowns). It can be concluded that CMP and GFP were satisfactory for restoring endodontically treated teeth after approximately 6 years of follow-up. Regarding coronary restoration, all-ceramic and metal ceramics crowns presented better clinical performance. In the second manuscript, a search was performed in PubMed, Scopus, Web of Science, LILACS, BBO, Cochrane Library, IADR abstracts, records of unpublished studies, dissertations and theses. Randomized clinical trials reporting failure rates separately for anterior and posterior teeth treated with post-and-core restorations were considered eligible. Two reviewers performed article selection, data extraction, and bias risk assessment using the Cochrane tool. Of the 2526 articles identified, 6 were selected and included in the metaanalysis (4 with uncertain risk of bias and 2 with low risk of bias). The heterogeneity was assessed by the Cochrane Q test and the I2 statistic, with a random effect model. The analysis of the subgroups considered anterior, posterior and post. The relative risk (RR) for failure rate between anterior x posterior teeth was 1.06 (95%CI=0.69-1.64, p=0.79), for canine x incisors 3.08 (95%CI=0.56-17.04, p=0.20), for pre-molars x molars 0.45 (95%CI=0.12-1.74, p=0.25), for glass fiber posts 1.13 (95%CI=0.61-2.09, p=0.70) and for cast metal post 1.10 (95%CI=0.64-1.91, p=0.72). It can be concluded that the failure rate in anterior and posterior teeth treated with post-and-core restorations was similar.